Sistem Penjualan Roti Dapur Anita Berbasis Web - Three Dyah Oktaviani; Teguh Khristianto (LPPM STIKOM Tunas Bangsa, 2023)
Online shop sales are a business that helps customers easily choose products without having to visit a store or be able to order anywhere and anytime. Anita's Kitchen online store is a bakery business that specializes in selling various types of bread, such as wet bread, dry bread, and snacks. Sales activities at Anita's Kitchen still use a simple method in the process of disseminating information using social media Instagram and Facebook for orders still manually via WhatsApp and coming directly to the place to confirm orders, and for monthly reports they are still manually recorded in a notebook. Thus causing product marketing to be not optimal, and customers having difficulty in obtaining bread product information, and monthly reports have not been computerized. Based on the following conditions, a website-based system is needed for Anita's Kitchen. The system built is related to the use of the method, namely RAD (Rapid Application Development), PHP Mysql programming language, then blackbox testing. With the existence of a website-based system at Anita's Kitchen, it is hoped that it will make it easier for customers to order online, and get the latest information about the quality, types, variants, tastes, and prices offered by Anita's Kitchen Bakery. And optimizing computerized services at Anita's Kitchen Bakery.